Influence of a flame-retardant on the fire-behaviour and the residual mechanical properties of C/PEKK composite laminates exposed to a kerosene flame. (January 2022) - Vieille, B.; Coppalle, A.; Le Pluart, L.; Schuhler, E.; Chaudhary, A.; Rijal, B.; Alia, A.; Delpouve, N.; Bourdet, A.
Abstract: This work examines the influence of a phosphorus-based flame-retardant additive (Exolit) on the fire-behaviour and the residual mechanical properties of composite laminates manufactured by a thermo-consolidation process from unidirectional (UD) carbon fibers (C) and a PEKK (Polyether-ketone-ketone) thermoplastic associated with or without Exolit. Depending on the laminates lay-up (orthotropic or quasi-isotropic), the influence of Exolit on the thermal degradation, resulting from a kerosene flame exposure (116 kW/m 2 and 1100 °C), on the composites structural integrity was examined. The changes in the residual tensile properties (axial stiffness and strength) were compared with respect to the virgin materials (experiencing no prior flame exposure) in room temperature (RT) conditions post fire exposure. The discussions on fire- and mechanically-induced damage mechanisms are supported by fractographic analysis of specimens. It is therefore possible to better understand how the fire-induced damages within the laminates micro- and meso -structures modify the mechanical behaviour of flame-exposed laminates. Thus, the axial stiffness and strength decrease moderately (−6% and −18%, respectively) in quasi-isotropic laminates with respect to virgin specimens. In orthotropic laminates, the axial stiffness decreases by 15%, whereas the axial strength dramatically decreases (−55%). The obtained results suggests that the flame-retardant additive not only delays the thermal degradation of C/PEKK laminates but also efficiently contributes to maintain the structural integrity of the composites, hence resulting in good mechanical properties. The positive effect of Exolit is particularly noticeable in orthotropic laminates whose mechanical behaviour is driven by 0° carbon fibers.